Transformative Role Of Education: An Autoethnographic Reflection (Research Nepal Journal of Development Studies, 2019)
This study appraised my momentarily missing twelve years of formal education life (1990-2002) and thoughtful higher education life (2002 to onward). Through this appraisal, I explored how I have been experiencing transformative role of education since my school education life. In so doing, I applied auto ethnography methodology and narrative imagination method for interpreting narrative information. While exploring my experiences, I found I was worry to improve my economic condition in the beginning. Thereby, I applied vocational rehabilitation therapy and resiliency against my frustration and engaged in working life that implicitly encouraged me to embark in higher educational voyage. However, later wards, I started worrying with poor socio-cultural and economic structures of own society and nation. Even my involvement in higher education/training and academic journeys in ever changing environment made me more critical, reflective and transformative because of my resilient will and inner urges. I successfully transformed my identity from rural development graduate to educationist and academician. Finally, this study also revealed that I was/am an exceptional student because of my good educational achievement. Hence, my reflections on transformative role of education are equally important to the students, teachers and development stakeholders for plying institutional agentic role to mobilize rural development graduates in local levels.